Mechanisms of hesperetin in treating metabolic dysfunction-associated steatosis liver disease via network pharmacology and in vitro experiments - Wu Yi; Lin Ying; Xu Shan; Su Dan; Yang Hao; Tang Lidan (Open Medicine)
Metabolic dysfunction-associated steatosic liver disease (MASLD) poses a global health challenge with limited therapeutic options. Hesperetin, a flavonoid extracted from citrus, exhibits multiple pharmacological properties, but its mechanisms in MASLD-associated lipid metabolism remain unclear. This study aimed to explore the mechanism of hesperetin for treating MASLD.